TacticUP Video Test for Soccer: Development and Validation - Machado, Guilherme; da Costa, Israel Teoldo (Frontiers in Psychology, 2020)
This study aims to expand the process of tactical assessment of soccer players, through the development and validation of a video-based test based on core tactical principles of play. The TacticUP video test for soccer is composed of offensive and defensive video sequences of 11vs11 soccer situations. Participants should choose the most appropriate solution for each video sequence. Content validity was established based on a panel of nine experts from four different countries. Construct validity was assessed through the comparison between players with distinct expertise levels. Comparisons between groups’ final scores showed statistical differences (P < 0.05) in ten out of the 15 variables assessed, in which the expert group displayed higher values compared to the non-expert group. Face validity examined the acceptability and suitability of the test by players. Reliability was determined through the test-retest method for each video sequence, and Cohen’s Kappa values ranged from .622 to 1.0. Therefore, the TacticUP video test showed adequate content, construct, and face validity and was a reliable measure of perceptual-cognitive and decision-making skills in soccer. We overcame limitations from previous video-based tests in soccer by introducing situations concerning off-the-ball movements, in both offensive and defensive phases. The practical applications of this test are: i) it can be used to monitor players’ perceptual-cognitive and decision-making skills; ii) the test is based on player’s response selection in a video-based test, which enables the measurement of their perceptual-cognitive and decision-making skills based on the core tactical principles of play; iii) generate players’ tactical profile considering their perceptual-cognitive and decision-making skills based on core tactical principles of play; and iv) measure the effectiveness of intervention/training programs on the development of perceptual-cognitive and decision-making skills.